THE EFFECT OF DIFFERENT VALUE CONCENTRATION ON SPIRULINA PLATENSIS TOWARD THE BRIGHTNESS OF COLORS ON GOLDFISH (CARASSIUS AURATUS) - Sary Astuty Aceh; Riza Rahman Hakim; Hariyadi Hariyadi (Universitas Muhammadiyah Malang, 2023)
Body coloration is one of the most important quality attributes determining the ornamental value of goldfish (Carassius auratus). Since fish are unable to synthesize carotenoids, dietary supplementation with natural carotenoid sources is required to enhance pigmentation. Spirulina platensis is a microalga rich in carotenoids that has the potential to improve fish coloration. Therefore, this study aimed to evaluate the effect of different concentrations of Spirulina platensis meal in feed on the color enhancement of goldfish. The study employed an experimental method using a Completely Randomized Design (CRD) consisting of six treatments with three replications. The treatments included feed supplemented with 0% (control), 1%, 2%, 3%, 4%, and 5% Spirulina platensis meal. Fish were reared for four weeks, and color intensity of the head, body, fins, and tail was assessed periodically. Water quality parameters, including temperature, pH, and dissolved oxygen (DO), were also monitored throughout the experiment. Data were analyzed using analysis of variance (ANOVA) followed by Duncan’s multiple range test. The results showed that dietary supplementation with Spirulina platensis significantly affected body coloration but had no significant effect on the coloration of the head, fins, and tail. The highest body color intensity was observed in fish fed diets containing 3% Spirulina platensis, with an average color score of 56.55 ± 0.59, significantly higher than the control treatment. Water quality remained within suitable ranges for goldfish culture, with temperatures of 23–26°C, pH 7, and DO ranging from 6.7 to 9.9 mg/L. In conclusion, supplementation of 3% Spirulina platensis meal in feed effectively enhances the body coloration of goldfish and can be recommended as a natural pigment source in ornamental fish culture.